Invasive Dreissena Mussel Coastal Transport From an Already Invaded Estuary to a Nearby Archipelago Detected in DNA and Zooplankton Surveys - Larson, Courtney E.; Barge, Jonathan T.; Hatzenbuhler, Chelsea L.; Hoffman, Joel C.; Peterson, Greg S.; Pilgrim, Erik M.; Wiechman, Barry; Rees, Christopher B.; Trebitz, Anett S. (Frontiers in Marine Science, 2022)
Coastal waters of Lake Superior are generally inhospitable to the establishment of invasive Dreissena spp. mussels (both Dreissena polymorpha and Dreissena bugensis). Dreissena have inhabited the Saint Louis River estuary (SLRE; largest commercial port in the Laurentian Great Lakes) for over three decades, but only in the last few years have small colonies been found in the Apostle Islands National Lakeshore (APIS, an archipelago situated 85 km to the east of SLRE) A 2017 survey determined a low abundance Dreissena spatial distribution in APIS, with the largest colonies on the north and west islands which suggested potential veliger transport from the SLRE via longshore currents. Our objective in this study was to determine if Dreissena veligers are transported by currents at low densities along the south shore of Lake Superior from the SLRE to APIS. To do so, we used both eDNA (water and passive substrate samples) and zooplankton collection methods at eight sites evenly spaced between the SLRE and APIS with three sampling times over five weeks. Dreissena veligers were consistently detected along the south shore, although at low abundances (veligers per m3 range = 0–690, median = 8), and for every 1 km increase in distance from the SLRE, both veliger counts and water eDNA copy numbers decreased on average by 5 and 7%, respectively. D. polymorpha (suited to estuary habitats) was detected two times more than D. bugensis (better suited to deep-lake habitats). There was not a trend in the veliger size distribution along the south shore, and temperature and calcium concentrations fluctuated around the threshold for Dreissena veliger and adult development, averaging 11.0°C and 14.8 ppm, respectively. Three zooplankton taxa representative of the estuary community–Daphnia retrocurva, Diaphanosoma birgei, and Mesocyclops copepodites–decreased as the distance from the SLRE increased mirroring Dreissena veliger abundance patterns. Findings represent multiple sources of evidence of a propagule “conveyor belt” for Dreissena along the south shore of Lake Superior. We conclude that veligers are functioning as a propagule, using coastal currents to spread from the point of invasion, thereby traversing coastal habitat previously reported as inhospitable to distant habitats suitable for colonization.